The effect of operator-induced variability on the physical properties of ProRoot MTA - TÜRKAYDIN, DİLEK (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Aims: The aim of this study was to compare the influence of operators on the microhardness and compressive strength of mineral trioxide aggregate (MTA). Materials and Methods: Forty dental specialists were asked to prepare a series of MTA samples. The tested material was ProRoot MTA (DentsplyMaillefer, Switzerland). Each participant prepared one sample to a consistency they considered acceptable for use in practice (improvised group) and another one according to the manufacturer's recommended water-to-powder (WP) ratio (pre-weighed group). The samples were incubated at 37 degrees C and 95% humidity for 4 days. Parameters evaluated in this study were microhardness and compressive strength. Results: Operators mixed MTA samples with varying WP ratios. However, there was no significant difference between the microhardness and compressive strength values of MTA samples between the improvised, the pre-weighed and the control groups. MTA was mixed in a thicker consistency than the manufacturers recommended ratio (0.33) by 62.5% of the operators. Conclusion: According to the results of this study, even though the WP ratios that were utilized in the clinical setting vary, microhardness and compressive strength values of MTA was not significantly affected.
Keywords: Compressive strength; microhardness; MTA; surface microhardness; water-to-powder ratio; MINERAL TRIOXIDE AGGREGATE; IN-VITRO EVALUATION; OUT BOND STRENGTH; TO-WATER RATIO; COMPRESSIVE STRENGTH; PLACEMENT TECHNIQUES; CEMENT; SOLUBILITY; POROSITY